Experimental Analysis of the Performance of Savonius VAWT with Different Numbers of Blades on Roofs - Francisco, Jeremi; Rhakasywi, Damora; Fahrudin, Fahrudin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Renewable energy is increasingly vital for sustainable development, with wind energy offering significant potential in urban settings where land availability is limited. Specific Background: Vertical axis wind turbines (VAWTs), particularly Savonius types, are promising for rooftop applications but remain underexplored compared to horizontal axis turbines. Knowledge Gap: Limited studies have systematically examined how variations in blade number affect VAWT performance under low wind speed conditions typical of urban environments. Aim: This study investigates the performance of Savonius VAWTs with 3, 4, and 6 blades to determine the optimal configuration for efficient energy generation on building roofs. Results: Experimental testing over 24 hours at an average wind speed of 2 m/s revealed that the 3-blade turbine achieved the best performance, with a tip speed ratio (0.94), coefficient of power (0.242), and voltage output (14.41 V), outperforming the 4-blade and 6-blade designs. Novelty: This work demonstrates that reducing blade count can enhance efficiency in low-speed, rooftop urban wind applications, challenging the assumption that more blades inherently improve performance. Implications: The findings provide insights for optimizing small-scale renewable energy systems in urban areas, contributing to sustainable energy strategies and supporting national renewable energy targets. Highlights: Three-blade Savonius turbine shows highest efficiency at low wind speeds. Blade number directly affects TSR, CP, and voltage output. Rooftop VAWT offers practical solution for small-scale urban energy. Keywords: Wind, Wind Turbine, Tip Speed Ratio, Energy, Green Energy